Abundance and physical controls of Mediterranean micro-estuaries - Yair Suari; Gitai Yahel; Gerardo Diaz; Hadar Zedaka; Tal Sade; Tal Amit; Tomer Blumenfeld; Merav Gilboa; Tal Ozer; Tom Topaz (Frontiers in Marine Science, 2026)
Introduction Estuaries, transitional zones between freshwater and the sea, are vital to global coastal ecology, support biodiversity, and provide ecosystem services. Estuarine research has often focused on larger systems while smaller estuaries (micro-estuaries) remain understudied. Herein, we define micro-estuaries by their hydrological and physical characteristics and investigate their abundance in the Mediterranean Sea, a region experiencing increasing anthropogenic pressure and the impacts of climate change. Methods Using bathymetric surveys and high-resolution temperature and salinity measurements, conducted in seven East Mediterranean micro-estuaries during the years 2014 -2024, we characterized the physical properties of micro-estuaries and established criteria for their identification. Next, we used GIS techniques to identify potential micro-estuaries across the Mediterranean, verified them on satellite imagery, and compared these findings with a published database of estuary locations. Results We identified a high abundance of micro-estuary-like outfalls throughout the Mediterranean (243 in total), about half of which are undocumented as estuaries and are therefore likely not managed as such. Although these systems are small (1 -7 km long, <3 m depth), they were highly stratified; the level of stratification and water quality were the key determinants of biogeochemical conditions such as oxygenation and denitrification. Water column structure was, in turn, controlled by sandbar morphology and freshwater inflow: most of these estuaries are intermittently connected to the sea and appear to be governed by a seasonally built sandbar that, together with the terrestrial freshwater inflow regime, defines the micro-estuary's function. Residence times of freshwater, seawater, surface water, and bottom water varied widely, from days to several months, reflecting these differences in hydrography and seasonality. Discussion Because micro-estuaries are particularly susceptible to anthropogenic modification, altering the inflow and manipulating the outfall shape are cost-effective managerial tools unique to these systems. The proximity of micro-estuaries to dense urban populations and the significant knowledge gaps highlight the need for further research on micro-estuaries globally.

A consensus-based, revised and comprehensive catalogue for Mediterranean water masses acronyms - KATRIN SCHROEDER; SANA BEN ISMAIL; MANUEL BENSI; ANTHONY BOSSE; JACOPO CHIGGIATO; GIUSEPPE CIVITARESE; FRANCESCO FALCIERI M; GIANNETTA FUSCO; MIROSLAV GAČIĆ; ISAAC GERTMAN; ELISABETH KUBIN; PAOLA MALANOTTE-RIZZOLI; et al. (Mediterranean Marine Science, 2024)
Addressing the need for clear communication in Mediterranean oceanography, this study presents a revised and comprehensive catalogue of water mass acronyms. Although there is no universal set of standard rules for assigning acronyms to water masses, as these can vary among different research groups, regions, or scientific communities, scientists generally aim for clarity and consistency when naming and abbreviating water masses to facilitate communication within the scientific community. The team of experts, guided by the CIESM (the Mediterranean Science Commission) C2 Committee on the Physics and Climate of the Ocean, reviewed existing literature and established new acronyms and naming guidelines. This standardized system, emphasizing clarity and consistency, replaces the current variable practices employed by different research groups.

Plume dispersal of a hyper-eutrophic micro-estuary to the eastern mediterranean during base flow and flood events - Boneh Shira; Topaz Tom; Ozer Tal; Yair Suari (Estuarine, Coastal and Shelf Science, 2023)

Observations of turbidity currents in a small, slope-confined submarine canyon in the Eastern Mediterranean Sea - Roy Jaijel; Eli Biton; Yishai Weinstein; Tal Ozer; Timor Katz (Earth and Planetary Science Letters, 2023)

Twenty years of in-situ monitoring in the south-eastern Mediterranean Levantine basin: Basic elements of the thermohaline structure and of the mesoscale circulation during 1995-2015 - George Zodiatis; Steve Brenner; Isaac Gertman; Tal Ozer; Simona Simoncelli; Marinos Ioannou; Sotiris Savva (Frontiers in Marine Science, 2023)
The in-situ data gathered over two decades since mid-1990s in the South-Eastern Levantine Basin from 34 hydrographic campaigns and from 35 bi-weekly and monthly Voluntary Observing Ships (VOS) transects, after the pioneering POEM cruises, have provided insight on the dominant meso-scale coherent circulation features of this sub-basin. The most pronounced feature, the anticyclonic Cyprus Eddy, migrates over the broad region of the Eratosthenes seamount and exhibits significant seasonal and inter-annual spatial-temporal variability. Another prominent structure of the sub-basin is the anticyclonic Shikmona Eddy generated by instabilities of the strong northward flowing jet along the south-easternmost shelf and slope of the Levantine basin. Its evolution and co-existence with the Cyprus Eddy, cause the periodic re-establishment of the Shikmona Gyre, which was first observed during the POEM cruises in mid-1980s. The offshore, cross basin, eastward flowing Mid-Mediterranean Jet (MMJ) defines the northern and southern flanks of these sub-basin scale anticyclonic eddies and transports the lower salinity Modified Atlantic Water (MAW) in the subsurface layer, through the warmest and most saline waters of the Mediterranean. Periodically, the MMJ bifurcates and/or is diverted northward, along the western coast of Cyprus due to westward and northward spatial fluctuations of the Cyprus Eddy’s western boundaries. The current long term in-situ monitoring of the sub-basin provides an overview of the extent of the main water masses and characterizes their variability throughout the period considered. The analysis of the data indicates an increase of the temperature and salinity of the Levantine Surface Water (LSW) and of the subsurface MAW. The Eastern Mediterranean Transient Water (EMTW) is shown to occupy the deep cavities in the vicinity of the Eratosthenes seamount while its upper boundary was found to be lifted to shallower depths over a period of two decades.

Discovery and chemical composition of the eastmost deep-sea anoxic brine pools in the Eastern Mediterranean Sea - Barak Herut; Maxim Rubin-Blum; Guy Sisma-Ventura; Yitzhak Jacobson; Or M. Bialik; Tal Ozer; Muhedeen Ajibola Lawal; Asaf Giladi; Mor Kanari; Gilad Antler; Yizhaq Makovsky (Frontiers in Marine Science, 2022)
Deep-sea anoxic brine pools are unique and extreme, yet habitable environments. However, their extent and processes of formation are not fully understood. Using geophysical analysis and seafloor surveying, we discovered the eastmost brine pools known in the ultraoligotrophic Eastern Mediterranean Sea, at the Palmahim Disturbance offshore Israel (~1150 m water depth). These brine pools are located directly above a ~1km wide piece of the Messinian evaporites section, which was up thrusted to ~350 m below the seafloor. We sampled brines and short cores to characterize the chemical composition of several small (up to 5m diameter) anoxic, methanic and warm (21.6°C) brine pools and adjacent seafloor sediments porewater. The maximal salinities measured at the pools and adjacent porewater were 63.9 and 72 PSU, respectively. The brines are characterized by enriched Na and Cl concentrations by a factor of ~1.8 and depleted Mg, SO 4 , K and Ca contents by factors of circa 6, 3, 2 and ~1.3, respectively, compared to the ambient seawater. Relations of the major element concentrations reveal a mixing curve between seawater and enriched Na/Cl and depleted Mg/Cl, K/Cl and SO 4 /Cl end-members, and do not coincide with relics of fossil residual evaporated seawater. We propose their composition reflects: 1) dissolution of Messinian halite (NaCl) by seawater, supported by their low Br/Cl ratios; 2) additional small rise in Na/Cl ratios due to the impact of clay mineral dehydration or/and dissolution of trace (~1% of the Na) amounts of detrital trona (Na 3 H(CO 3 ) 2 •2H 2 0), coinciding with the enriched alkalinity concentrations; 3) diagenesis processes depleting Mg, K and SO 4 , mainly by the formation of authigenic K-rich Mg-smectite, clay mineral dehydration, dolomitization/Mg-calcite precipitation and redox processes. The δ 18 O and δD values of the Palmahim brine may reflect the impact of clay mineral dehydration. Comparison to all other East Mediterranean brine lakes shows that the Palmahim brine pool system represents similar provenance of brines as observed for the Eastern Mediterranean Napoli, Nadir and Tyro lakes, while potentially recording additional processes attributed to its proximity to the coastal area.

Influence of cyclonic and anticyclonic eddies on plankton in the southeastern Mediterranean Sea during late summertime - Natalia Belkin; Tamar Guy-Haim; Maxim Rubin-Blum; Ayah Lazar; Guy Sisma-Ventura; Rainer Kiko; Arseniy R. Morov; Tal Ozer; Isaac Gertman; Barak Herut; Eyal Rahav (Ocean Science, 2022)
Planktonic food webs were studied contemporaneously in a mesoscale cyclonic (upwelling, ∼ 13 months old) and an anticyclonic (downwelling, ∼ 2 months old) eddy as well as in an uninfluenced background situation in the oligotrophic southeastern Mediterranean Sea (SEMS) during late summer 2018. We show that integrated nutrient concentrations were higher in the cyclone compared to the anticyclone or the background stations by 2–13-fold. Concurrently, Synechococcus and Prochlorococcus were the dominant autotrophs abundance-wise in the oligotrophic anticyclone (∼ 300 × 1010 cells m−2). In the cyclone, functional groups such as dinoflagellates, Prymnesiophyceae and Ochrophyta contributed substantially to the total phytoplankton abundance (∼ 14 × 1010 cells m−2), which was ∼ 65 % lower at the anticyclone and background stations (∼ 5 × 1010 cells m−2). Primary production was highest in the cyclonic eddy (191 mgCm-2d-1) and 2–5-fold lower outside the eddy area. Heterotrophic prokaryotic cell-specific activity was highest in the cyclone (∼ 10 fgCcell-1d-1), while the least productive cells were found in the anticyclone (4 fgCcell-1d-1). Total zooplankton biomass in the upper 300 m was 10-fold higher in the cyclone compared with the anticyclone or background stations (1337 vs. 112–133 mg C m−2, respectively). Copepod diversity was much higher in the cyclone (44 species), compared to the anticyclone (6 small-size species). Our results highlight that cyclonic and anticyclonic eddies show significantly different community structure and food-web dynamics in oligotrophic environments, with cyclones representing productive oases in the marine desert of the SEMS.

Thermohaline Temporal Variability of the SE Mediterranean Coastal Waters (Israel) – Long-Term Trends, Seasonality, and Connectivity - Tal Ozer; Isaac Gertman; Hezi Gildor; Barak Herut (Frontiers in Marine Science, 2022)
The high variability of coastal waters together with the growing need for assessing the state of the marine coastal ecosystem, require continuous monitoring at exceptional resolution and quality, especially during the Anthropocene changing seas. We perform a comprehensive analysis of a decadal (March 2011 to June 2021) thermohaline variability of the East Levantine Basin (LB) coastal waters (continuous measurements), its predominating temporal trends and their linkage with atmospheric forcing and advection. We identify statistically significant long-term warming and salinification trends with yearly rates of 0.048°C and 0.006, respectively. Through the use of the X11-ARIMA method temperature and salinity inter-annual trends are examined and associated with previously published open ocean dynamics as well as model reanalysis. We study the linkage between Northern and Southern coastal locations, and identify the along shore northward current as a primary cause of positive temperature anomalies arriving from the south. The coastal salinity long-term trend demonstrates a connection to local precipitation. A less coherent seasonal sequence is found with a bimodal behavior, where, salinity values drop in August on several summers. This drop is attributed to the intensification of the along shore current in the period of June-July, potentially advecting more Atlantic Water. The observations presented here emphasize the relatively strong coupling between coastal water and the open ocean, the influence of the general surface circulation of the LB on the coastal zone and the faster response time and higher sensitivity of the coastal environment to atmospheric forcing.

Post-eastern Mediterranean Transient Oxygen Decline in the Deep Waters of the Southeast Mediterranean Sea Supports Weakening of Ventilation Rates - Guy Sisma-Ventura; Nurit Kress; Jacob Silverman; Yaron Gertner; Tal Ozer; Eli Biton; Ayah Lazar; Isaac Gertman; Eyal Rahav; Barak Herut (Frontiers in Marine Science, 2021)
Long-term trends in oxygen, salinity, and nutrients were followed in the Southeastern Mediterranean (SEMS) deep waters from 2002 to 2020. Results show a net decrease in oxygen since 2008 of −0.5 ± 0.1 μmol kg −1 yr −1 in the bathypelagic depths (1,200–2,000 m). Multiannual variability in oxygen levels superimposed this trend, and is likely associated with variations in thermohaline fluxes. The 2020 mean oxygen concentration of 179.5 ± 2.3 μmol kg −1 is comparable to the pre-Eastern Mediterranean Transient (EMT) mean value. The post-EMT signature is clearly demonstrated in both oxygen and salinity over the period of 2002–2013, but since 2014 it diminished, mainly due to mixing of the Aegean deep water (AegDW) mass with the overlying old Adriatic water mass. This trend reflects a switch back to the pre-EMT regime, characterized by thermohaline homogeneity of the deep water column in the SEMS. The long-term decline of deep water oxygen levels is also accompanied by a corresponding increase in dissolved inorganic nutrients, supporting aging of the deep water masses. Our results suggest that ventilation of the SEMS deep water is currently occurring at a lower, pre-EMT rate, probably as a result of moderated deep water formation in recent time.

Mesopelagic Prokaryotes Alter Surface Phytoplankton Production during Simulated Deep Mixing Experiments in Eastern Mediterranean Sea Waters - Or Hazan; Jacob Silverman; Guy Sisma-Ventura; Tal Ozer; Isacc Gertman; Efrat Shoham-Frider; Nurit Kress; Eyal Rahav (Frontiers in Marine Science, 2018)